majelis ta'lim sebagai media sosialis efektif pilkada yang adil dan jujur: local election, islamic study group, socialization media, democracy - Irnawati, Irnawati (Buana Pendidikan, 2015)
the implementation of local election was intended as one of the real implementation of the process of democratization.